Comprehensive Filling of Structural Elements of Value-Deontological Competences of Future it Specialists - Shlikhta, Ganna (Educological discourse, 2023)
The modern information society requires from future IT specialists not only technical expertise, but also a deep understanding of the ethical and value aspects of their professional activity. This article is devoted to the study of value-deontological competences in education and training of future information technology (IT) specialists. An analysis of the importance of meaningful filling of the structural elements of the studied competencies: axiological and deontological for future specialists in information technologies has been carried out. The article discusses the need to include ethical issues in training programs for information technology specialists and the meaningful development of its aspects. The role of ethics, professional responsibility and deontology in the work of IT specialists is considered in the light of the growing influence of technology on society. Some of the key issues addressed in the article include: the impact of technology on society and the need for future IT professionals to understand this impact and the importance of value orientations and professional ethics in working with users’ data and personal information. The concept of "axiological knowledge" and "deontological knowledge" is substantiated, and the content of these concepts in the structure of value-deontological competencies of the future IT specialist is clarified. The impact of the basic values of the individual in solving ethical conflicts and making responsible decisions in the field of information technologies is highlighted. Measures to integrate value-deontological aspects into the educational process for the training of future IT specialists are substantiated. This article helps to understand the importance of developing not only technical, but also ethical competences, basic values in the training of young IT specialists, contributing to increasing their professional responsibility and making a positive contribution to the development of the information society.